2020
DOI: 10.3390/jcm9061616
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Resorption of Liposomal Packed Vitamin C Monitored by Ultrasound

Abstract: Vitamin C is an essential nutrient for humans and is involved in a plethora of health-related functions. Several studies have shown a connection between vitamin C intake and an improved resistance to infections that involves the immune system. However, the body cannot store vitamin C and both the elevated oral intake, and the intravenous application have certain disadvantages. In this study, we wanted to show a new formulation for the liposomal packaging of vitamin C. Using freeze etching electron microscopy, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In addition, the body cannot store AA, and both the elevated oral intake and the intravenous application have certain disadvantages. Thus, as a novel approach, phospholipid-based oral delivery of AA might be a way to overcome these limitations mainly because lipid aggregates can prevent AA degradation in the gastrointestinal tract; thus, a raise of AA in the plasma level is observed after liposomal oral application of AA …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the body cannot store AA, and both the elevated oral intake and the intravenous application have certain disadvantages. Thus, as a novel approach, phospholipid-based oral delivery of AA might be a way to overcome these limitations mainly because lipid aggregates can prevent AA degradation in the gastrointestinal tract; thus, a raise of AA in the plasma level is observed after liposomal oral application of AA …”
Section: Resultsmentioning
confidence: 99%
“…Thus, as a novel approach, phospholipid-based oral delivery of AA might be a way to overcome these limitations mainly because lipid aggregates can prevent AA degradation in the gastrointestinal tract; thus, a raise of AA in the plasma level is observed after liposomal oral application of AA. 37 It is worth mentioning that the absorption of drugs depends on various factors including membrane permeability [indicated by a colon cancer cell line (Caco-2)], intestinal absorption, skin permeability levels, and P-glycoprotein substrates or inhibitors. 38 In the current study, AA was loaded in vesicles with fiber-reinforced phospholipids, which form a highly stable lipid bilayer in powdered formulation by fiber core formation.…”
Section: Encapsulation Efficiency (Ee)mentioning
confidence: 99%
“…This advantage has also been confirmed in a study by Prantl and co-workers in which vitamin C-containing liposomes were monitored in real time via ultrasound in the gastrointestinal tract of four healthy volunteers [ 219 ]. They observed a high uptake trough the duodenum and jejunum of liposomes, its good adherence to the intestinal wall, penetrating through the mucosa, and then its ability to reach the mesenteric vessels and liver in higher concentrations [ 219 ]. Indeed, clinical trials showed that oral liposomal vitamin C may be better at reducing the extent of multiple organ failure and may better improve the short-term outcomes of sepsis, counteracting the cytokine storm by inhibiting the production and release of pro-inflammatory cytokines IL-1β, IL-2, IL-6, and TNF-α from human monocytes of COVID-19 patients with severe symptoms [ 220 ].…”
Section: Natural Products and Nanotechnological Approach To Treating ...mentioning
confidence: 63%
“…The PDI values were close in magnitude, and exceeded 0.2 for liposomal vitamin C (0.2) and liposomal vitamin D3 (0.53), which indicated monodisperse and polydisperse particle size distributions, respectively [ 75 ]. Liposomes may vary in size, between 200–3000 nm for liposomal vitamin C, and 100–1000 nm for liposomal vitamin D3, which is related to multiple lipid layers, fusion or aggregation phenomena [ 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our results concur with those of a recent study of liposomal-based vitamin C that had been readily prepared with food grade materials and simple equipment, and which provided a well-tolerated natural health product. The uptake of ingested liposomes from the gut to the mesenterial vessels and liver vessels was supported by a microbubble-enhanced ultrasound (MEU) method with real-time imaging [ 76 ]. Similarly, liposomes with a well-defined size distribution were used to achieve efficient absorption of hydrophobic vitamin D3.…”
Section: Discussionmentioning
confidence: 99%